The nurse anesthetist perioperative dialog - Anna Abelsson; Annette Nygårdh (BMC, 2020)
Abstract Background In the perioperative dialogue, pre-, intra- and postoperatively, the patient shares their history. In the dialogue, the nurse anesthetist (NA) gets to witness the patient's experiences and can alleviate the patients' suffering while waiting for, or undergoing surgery. The aim of this study was to describe the nurse anesthetist's experiences of the perioperative dialogue. Methods The study had a qualitative design. Interviews were conducted with 12 NA and analyzed with interpretive content analysis. The methods were conducted in accordance with the COREQ guidelines. Results In the result, three categories emerge: A mutual meeting (the preoperative dialogue) where the patient and the NA through contact create a relationship. The NA is present and listens to the patient, to give the patient confidence in the NA. In the category, On the basis of the patient's needs and wishes (the intraoperative dialogue), the body language of the NA, as well as the ability to read the body language of the patient, is described as important. In the category, To create a safe situation (the postoperative dialogue) the NA ensures that the patient has knowledge of what has happened and of future care in order to restore the control to the patient. Conclusion The patient is met as a person with their own needs and wishes. It includes both a physical and a mental meeting. In a genuine relationship, the NA can confirm and unreservedly talk with the patient. When the patients leave their body and life in the hands of the NA, they can help the patients to find their inherent powers, which allows for participation in their care. Understanding the patient is possible when entering in a genuine relationship with the patient and confirm the patient. The perioperative dialogue forms a safety for the patients in the operating environment.